Randomised, double-blind, placebo-controlled pilot trial of omeprazole in idiopathic pulmonary fibrosis. Issue 4 (4th January 2019) - Dutta, Prosenjit; Funston, Wendy; Mossop, Helen; Ryan, Vicky; Jones, Rhys; Forbes, Rebecca; Sen, Shilpi; Pearson, Jeffrey; Griffin, S Michael; Smith, Jaclyn A; Ward, Christopher; Forrest, Ian A; et al.
Abstract : Background: Cough is a common, disabling symptom of idiopathic pulmonary fibrosis (IPF), which may be exacerbated by acid reflux. Inhibiting gastric acid secretion could potentially reduce cough. This study aimed to determine the feasibility of a larger, multicentre trial of omeprazole for cough in IPF, to assess safety and to quantify cough. Methods: Single-centre, double-blind, randomised, placebo-controlled pilot trial of the proton pump inhibitor (PPI) omeprazole (20 mg twice daily for 3 months) in patients with IPF. Primary objectives were to assess feasibility and acceptability of trial procedures. The primary clinical outcome was cough frequency. Results: Forty-five participants were randomised (23 to omeprazole, 22 to placebo), with 40 (20 in each group) having cough monitoring before and after treatment. 280 patients were screened to yield these numbers, with barriers to discontinuing antacids the single biggest reason for non-recruitment. Recruitment averaged 1.5 participants per month. Geometric mean cough frequency at the end of treatment, adjusted for baseline, was 39.1% lower (95% CI 66.0% lower to 9.3% higher) in the omeprazole group compared with placebo. Omeprazole was well tolerated and adverse event profiles were similar in both groups, although there was a small excess of lower respiratory tract infection and a small fall in forced expiratory volume and forced vital capacity associated with omeprazole. Conclusions: A large randomised controlled trial of PPIs for cough in IPF appears feasible and justified but should address barriers to randomisation and incorporate safety assessments in relation to respiratory infection and changes in lung function.